Statement at the inauguration of the ILRI poultry facility by Koen Vanmechelen, artist of Incubated Worlds, Addis Ababa, Ethiopia, 26 April 2018 - Vanmechelen, K. (2018)
Speech presented at the Inauguration of Incubated Worlds, ILRI Addis Ababa, 26 April 2018